THE EFFECT OF JUSTICE SERVICES ON CUSTOMER LOYALTY IN PKU MUHAMMADIYAH HOSPITAL, YOGYAKARTA - Munawir Munawir (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
The number of research samples, one of which is closely related to data analysis techniques. This study was designed using structural equation modeling (SEM). According to Bentler and Chou (1987) the total sample size of 200 has met the requirements for research using multivariate analysis tools, namely 5 times as many research parameters. Meanwhile, to use the AMOS Data Splitting Program, a sample size of 100 to 200 is required (Ghozali, 2013). Based on the results of data analysis that has been carried out, it can be concluded that the effect of justice services on consumer loyalty at Rsu Pku Muhammadiyah Yogyakarta Based on table 4.1 it can be seen that all indicators in the variables namely Procedural Justice, Interactional Justice, Complaint, Customer Satisfaction and Consumer Loyalty are declared valid, because it has a loading factor value above 0.5 (CFA> 0.5).